Relationship between self-compassion, perfectionism, and body image satisfaction among university students in Malaysia - Chang, Dixon; Pua, Xin Ci; Ng, Shirley Sock Li (2019)
University students face many challenges such as body preoccupation, social comparison, and self-evaluation which cause them to be at risk of developing negative body image. Furthermore, limited studies are done to examine self-compassion within Malaysian context. Therefore, the objective of the present study is to identify the gender difference in selfcompassion among university students and to examine the unique predictor of body image satisfaction between self-compassion and perfectionism. This study was conducted using cross-sectional survey research design and convenience sampling to recruit participants. An online self-administered questionnaire was used to collect data on participant’s demographic information, self-compassion level, perfectionism and body image satisfaction. A pilot study was conducted prior to the actual study and showed high reliability for all three scales respectively: α= .758, α= .839, and α= .836. Independent t-test showed that there is no gender difference in self-compassion among university students while multiple linear regression analysis revealed that adaptive perfectionism was the most significant predictor of body image satisfaction. This study is able to provide implication to the counselors, university personnel and students in developing programs and interventions to assist students in reducing their body image dissatisfaction. This study also able to help students to recognize the effect of perfectionism on body image satisfaction and hence enhancing self-respect and appreciation towards own body.